2013
DOI: 10.1007/s13594-013-0109-6
|View full text |Cite
|
Sign up to set email alerts
|

Sensory properties and acceptance of Uruguayan low-fat cheese “queso magro”

Abstract: International audienceDue to health and overweight concerns, there is an increasing interest of consumers for low-fat food. The objective of this work was to study the differences in sensory properties of a Uruguayan low-fat cheese “queso magro” and to establish whether there is a relationship with its acceptability. Six samples of this type of cheese from different commercial brands were studied. The sensory properties of these cheeses were evaluated by a trained panel and subsequently sample acceptability wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…Conversely, there is evidence that bitterness is not a desirable cheese characteristic for some consumers, as reported by several authors (Arcia, Curutchet, Costell, & Tarrega, ; Bord, Guerinon, & Lebecque, ; Caspia et al, ; Young, Drake, Lopetcharat, & McDaniel, ; Zhang et al, ). A dislike for “bitter” taste has also been studied in other food products than cheese, such as whole‐grain products (Bakke & Vickers, ), extra virgin olive oils (Barbieri et al, ; Delgado & Guinard, ; Recchia, Monteleone, & Tourila, ) or green vegetables (Chadwick, Gawthrop, Michelmore, Wagstaff, & Methven, ; Dinnella et al, ; Poelman, Delahunty, & Graaf, ).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Conversely, there is evidence that bitterness is not a desirable cheese characteristic for some consumers, as reported by several authors (Arcia, Curutchet, Costell, & Tarrega, ; Bord, Guerinon, & Lebecque, ; Caspia et al, ; Young, Drake, Lopetcharat, & McDaniel, ; Zhang et al, ). A dislike for “bitter” taste has also been studied in other food products than cheese, such as whole‐grain products (Bakke & Vickers, ), extra virgin olive oils (Barbieri et al, ; Delgado & Guinard, ; Recchia, Monteleone, & Tourila, ) or green vegetables (Chadwick, Gawthrop, Michelmore, Wagstaff, & Methven, ; Dinnella et al, ; Poelman, Delahunty, & Graaf, ).…”
Section: Resultsmentioning
confidence: 86%
“…In the study on Cheddar cheese, Caspia et al () demonstrated that texture could not be used to relate descriptive sensory analysis to consumer acceptance, whereas flavor characteristics fitted well with it. Arcia et al () showed that differences in flavor dictated the differences in consumers' acceptance of Uruguayan “queso magro” low‐fat cheese. Other authors, has also determined that flavor was more a driving force in overall liking of different cheeses (raw milk cheeses) than texture (Liggett, Drake, & Delwiche, ; Yates & Drake, ; Young et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Si bien el precio y el nivel de ingreso influyen en la decisión de compra, otros factores, intrínsecos del producto, podrían tener una mayor influencia sobre la decisión, pero esto implica que el consumidor tenga la posibilidad de conocer a fondo el producto. Diversos trabajos establecen que el sabor es el atributo más importante para determinar la calidad y la disposición a comprar un alimento local, pero sólo está disponible cuando se vive la experiencia sensorial, mientras que otros factores como precio, marca, presentación y el hecho de que sea artesanal o local, entran en juego cuando no se conoce nada más del producto (2,30,31) . Después de que los panelistas eligieron el queso preferido y manifestaron intención de compra, se indagó por las principales motivaciones para comprarlo, y se encontró que el sabor fue el atributo más importante para 55.4 % de los panelistas, 20.7 % porque lo consideró único y artesanal, 24 % por factores como presentación, curiosidad y por ser un producto local, y sólo 6.5 % lo comprarían por el precio.…”
Section: Intención De Compra Y Disposición a Pagar Un Precio Diferentunclassified